2012
DOI: 10.4314/wsa.v38i5.2
|View full text |Cite
|
Sign up to set email alerts
|

The performance of plant species in removing nutrients from stormwater in biofiltration systems in Cape Town

Abstract: In 2009, the City of Cape Town (CoCT) adopted a stormwater policy which mandates that new and existing developments should reduce the concentration of phosphorus and suspended solids in stormwater runoff by 45% and 80%, respectively, but offered no explicit guidance about how these water quality targets might be achieved. This study aims to contribute to the limited knowledge that exists about the performance of local plant species to treat stormwater. A large nursery-based study was conducted to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
1
15
1
Order By: Relevance
“…The removal efficiency ranged between 65 and 96% (average removal 87%), whilst the soil control removed 59%, on average. In contrast to the findings of previous research (Bratieres et al, 2008;Read et al, 2008;Milandri et al, 2012), this study showed far greater NO 3 -N removal. These contrasting findings may be the result of the specific plant species under study, micro-organisms, the establishment of bacterial assemblages in the rhizosphere, and the drip irrigation applied as opposed to rapid high volume irrigation (Bratieres et al, 2008;Read et al, 2008).…”
Section: Nitrate (Mg/l N)contrasting
confidence: 99%
See 1 more Smart Citation
“…The removal efficiency ranged between 65 and 96% (average removal 87%), whilst the soil control removed 59%, on average. In contrast to the findings of previous research (Bratieres et al, 2008;Read et al, 2008;Milandri et al, 2012), this study showed far greater NO 3 -N removal. These contrasting findings may be the result of the specific plant species under study, micro-organisms, the establishment of bacterial assemblages in the rhizosphere, and the drip irrigation applied as opposed to rapid high volume irrigation (Bratieres et al, 2008;Read et al, 2008).…”
Section: Nitrate (Mg/l N)contrasting
confidence: 99%
“…The IAP species were selected for their current use in constructed wetlands, wastewater treatment facilities, SuDS and biofiltration treatment trains. These species (Table 2) have proven excellent remediators of polluted water, and are commonly used internationally (Schachtschneider et al, 2010;Milandri et al, 2012).…”
Section: Plant Selection For Phytoremediationmentioning
confidence: 99%
“…It was also demonstrated that higher content of water and fertilizer does not benefit plant growth. Furthermore, plant type is an important factor that affects nutrient runoff, absorption of nutrients, permeability and porosity of the substrate material, and the effects of plant roots on the soil microbial community [44]. In the second year, plant biomass of A. fruticosa becomes relatively stable, the plant's demand for nutrients is reduced, and the major elements accumulated in the substrate are gradually released in the runoff [45].…”
Section: Comprehensive Appraisal Of Optimal Conditions Of Water and Fmentioning
confidence: 99%
“…Studies in China [33] showed that bioretention systems led to reductions in water volume and peak flow rates of 59-68% and 72-86%, respectively. Additionally, there is indication [34] that some plant species (mostly grasses) can reduce average concentrations of phosphates by 81%, ammonia by 90% and nitrates by an average of 69%. Most phosphate and ammonia treatment occurred within the soil medium.…”
Section: Bioretention Systemsmentioning
confidence: 99%
“…For the case of TP, the removal performance is effective in both laboratory and site studies, with a removal rate of 65 to 97%. For TN, removal performance rates present too wide ranges, from 1% (Hsieh and Davis, 2005) to 99% (Milandri et al 2012). Investigations [36] indicated that high nutrient and metals removal rates can be achieved over a range of hydraulic conductivities using designed mixes of recycled organic and mineral materials.…”
Section: Bioretention Systemsmentioning
confidence: 99%